Strategic asset valuation: A model including asymmetry and kurtosis in its distribution in continuous time - Milanesi, Gastón (2015)
The valuation of real assets is a complex problem which influences the strategic decision making in companies, such as decisions to differing or selling a project. Uncertainty takes over the manager when defining the attributes of the density function representing values that could assume the asset in the future. In this issue, we include not only its mean and variance, but also stochastic higher moments of this function (asymmetry and kurtosis). This paper proposes to valuate this type of entrepreneurships using real options theory making adjustments that allow us to abandon the assumption of normal returns in continuous time. This technique permits the expansion’s coefficient to depend also on the higher moments, either the original distribution or the approach one. Therefore, we obtained theoretical solutions to asset valuations that would have been impossible to solve.